Application of Geographic Information System (GIS) in Watershed Runoff Analysis: Case Study of Sungai Pangsun Watershed, Ulu Langat, Selangor - Tan, Teck Hock (2002)
This study aims at developing a GIS aided analysis to generate watershed runoff data. For this purpose, the Sg. Pangsun watershed, a small headwater catchment located in Ulu Langat, Selangor was chosen as an experimental ground. This basin has an area of approximately 2.6 km2 and lies on the southern flank of the Main Range. Two GIS-based software namely ARC/INFO 3.4 and ArcView 3.1 with Spatial Analyst 1.1 a, 3D-Analyst and the Hydrology extensions were applied in this study. The former was employed to create three digital coverages of geographical features, namely, stream, contour and boundary from topographic maps to be used as database by the latter to perform spatial and hydrological analyses which generated three intended themes, namely, grid slope, flow accumulation and stream network. The grid slope theme provided slope values for the calculation of overland and channel flows travel times on cells concerned using continuity-momentum and Manning-continuity principles respectively. The flow accumulation theme on the other hand delineated the main channel of the study watershed whose water on its cells considered as channel flow. The stream network theme provided the flow path of runoff (distance) for computation of the various time units taken by runoff from cells of both overland and channels flows to travel to the watershed outlet. The cells (partial watershed areas) were then categorized based on their travel times to produce the time-area histogram that represents the translation effect of runoff (equilibrium flow) on watershed surface. Clark's Instantaneous Unit Hydrograph method was later used to take into account the storage effect of the study watershed (delay caused by surface detention, saturation of soil profile, etc.) to produce a 15- minute unit hydro graph (UH).